848. PLATYSTELE MISERA: Orchidaceae. (December 2016) - Dodsworth, Steven
Summary: Platystele misera (Lindl.) Garay is illustrated as the first of two species of Platystele Schltr., a genus of tiny Pleurothallid orchids from South and Central America. The ecology and distribution of Platystele are discussed, accompanied by brief notes on the cultivation of this species.